(untitled) (Journal of Economic Research & Business Administration, 2022)
The reconstruction of areas recognized as socially important involves the integration of private capital into these sectors, and this is becoming a worldwide trend. Public-private partnership (PPP) opens a wide range of opportunities in healthcare, such as the introduction of innovative methods of treatment, technical equipment of polyclinics, improving the quality of medical services, technical, methodological modernization of laboratory centers in education. The importance of this problem for the economy of the country emphasizes the relevance of the study direction. The main purpose of the article is to provide ways to accelerate the development of the social orientation of country`s infrastructure through the mechanisms of public-private partnerships. In practice, the definition of the application of PPP mechanisms in general allows to determine that the digital Kazakh society becomes an important tool in its creation. These issues actualize the need to create a partnership between the state and the private sector and the application of solid experience on them. Theoretically, this article can serve as a basis for the development of a methodology for establishing a mutual partnership between the state and the private sector. Statistical analysis, the method of aggregate (integral) capacity, and review and analytical methods were used in the research. The methodology of public-private partnership developed according to its modern significance will allow to determine the rational use of possibilities of private sector in solution of actual problems of national economy, to improve the state organization of modes of people’s use of public goods, to modernize infrastructure, to accelerate construction of model of bilateral rationality and efficiency in optimal solution of issues of economy diversification. Key words: public-private partnerships, social projects, public-business partnerships, risks.